Early risk factors for acute chest syndrome in sickle cell anemia: A pediatric study - Mohamed Condé; Florie Bouvier; Roselyne Brat; Salim Ferrani; Régis Hankard; Philippe Connes; Georges Dimitrov (PLoS ONE, 2025)
Acute chest syndrome (ACS) is a life-threatening complication of sickle cell anemia (SCA). Most often, ACS occurs during the progression of a painful vaso-occlusive crisis (VOC) in vulnerable patients. The present study aimed to identify early risk factors for ACS progression, focusing on patient assessments in a pediatric Emergency Department. In this study (2016–2022) concerning exclusively the SS and Sβ 0 sickle cell disease genotypes, severe VOC encounters progressing to ACS were compared to uncomplicated severe VOCs. Medical history, clinical and laboratory data were collected for both groups. Out of 280 severe VOC encounters without initial respiratory symptoms, 40 progressed to life-threatening acute chest syndrome. The forty ACS (age 8.5 ± 4.3 years, 37% females) were compared with 240 severe VOCs (9.3 ± 4.4 years, 46% females). ACS was positively correlated with the occurrence of VOC at night, diffuse (multifocal) pain and increased C-Reactive protein (p < 0.05). The multivariable modelling, using generalized linear mixed-effects models, defined three risk factors for ACS occurrence: diffuse pain, night-time pain occurrence, and increased C-Reactive protein (p < 0.01). Increased use of opiates in the Emergency Department, elevated total leucocyte count, breath rate, and decreased red blood cell count were not significantly associated with ACS occurrence (p > 0.05). The initial evaluation of SCA patients’ acute pain in the Emergency Department is crucial for subsequent management during hospitalization.